Evaluasi Kondisi Tahanan Isolasi House Service Transformer Pada Power Station PLTA Peusangan - Muhammad Fikri Kurniawan Sitorus; Rizky Akbar Yuzakhri; Helmi Alfianza; Desman Jonto Sinaga (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to evaluate the condition of the House Service Transformer (HST) insulation at No. 1 Power Station PLTA Peusangan during the pre-operational stage. The testing was conducted directly in the field using a Megger Insulation Tester MIT 525 with a DC voltage of 5 kV on the HV side and 1 kV on the LV side to obtain the Insulation Resistance (IR) values in the HV–LV, HV–ground, and LV–ground configurations, as well as the Polarization Index (PI) on the HV-LV side. The IR measurement results were 42.2 GΩ, 17.43 GΩ, and 5.45 GΩ at a temperature of 36.0 °C and humidity of 95.3%, all of which were well above the minimum reference limit of 100 MΩ. The PI value obtained was 1.20, which was interpreted with caution because the insulation resistance in the first minute was already in the order of gigaohms, so PI was more appropriately positioned as a supporting parameter. Overall, the test results showed that the HST insulation system was still in very good condition and suitable to support the operational readiness of the internal electrical system of the hydroelectric power plant.